Mongolian Monastery Erdeni-zu: History and Modernity (Results of an Expedition) - T. P. Vanchikova; N. D. Tsyrenova (Научный диалог, 2023)
The history of Erdeni-dzu, the first stationary Buddhist monastery in Mongolia, founded in 1585—1586, is considered, and attention is paid to its current state. The relevance of the study is due to insufficient knowledge of the history of individual monasteries that played an important role in the spread of Buddhism, which include Erdeni-dzu, which was a model for other Mongolian monasteries and had a cultural significance in the ethnic history of the people. The novelty of the study is seen in the conclusion that the first monks — Tibetan lamas, who belonged to the Sakyapa school, contributed to the Mongolian lamas in the study and development of the fullness and integrity of the Buddhist theological tradition. They supported the creation of the actual Mongolian monastic community — the sangha, which, until the closure, the Erdeni-dzu monastery was one of the religious, cultural and economic centers of Khalkha-Mongolia. It is reported that in the 30s of the XX century the monastery was closed, in 1944 it was taken under state protection, in 1947 it was transformed into a museum. According to field data obtained by the authors in 2022, it is one of the most actively visited tourist centers and continues to be one of the main factors in the preservation of the cultural heritage of the Mongolian people.